فاعلية التعلم المدمج لتنمية مهارات برمجة الرسوم المتحركة التعليمية لدى تلاميذ المرحلة الإعدادية - الخطيب، نجلاء شعبان كمال; أمين، أمين صلاح الدين; الشربيني، زينب حسن حسن (جامعة المنصورة - كلية التربية, 2023)
هدف هذا البحث إلى تنمية مهارات برمجة الرسوم المتحركة التعليمية لدى تلاميذ المرحلة الإعدادية من خلال تطوير بيئة التعلم المدمج، وتم استخدام المنهج الوصفي التحليلي في مرحلة الدراسة والتحليل، والمنهج التجريبي لقياس أثر تطوير بيئة التعلم المدمج لتنمية مهارات برمجة الرسوم المتحركة التعليمية لدى تلاميذ المرحلة الإعدادية، وتم استخدام أدوات البحث الحالي وهما: الاختبار التحصيلي لقياس الجوانب المعرفية، وبطاقة الملاحظة لقياس الجوانب الأدائية، وتم عرض فروض البحث وإجراءاته، وتم اختيار عينة البحث، حيث اقتصر البحث الحالي على عينة من طلاب الصف الأول الإعدادي بمدرسة كفر سعدون للتعليم الأساسي بإدارة قطور التعليمية مديرية التربية والتعليم بالغربية، وتم استخدام مجموعة تجريبية، وتم تطبيق القياس القبلي والبعدي على للمجموعة التجريبية، أسفرت النتائج عن وجود فرق دال إحصائياً عند مستوى دلالة (0.05) بين متوسطي رتب درجات المجموعتين لصالح المجموعة التجريبية في التطبيق البعدي لبطاقة الملاحظة، ووجود فرق دال إحصائياً عند مستوى دلالة (0.05) بين متوسطي رتب درجات المجموعتين لصالح المجموعة التجريبية في التطبيق البعدي لاختبار التحصيل المعرفي، ووجود فرق دال إحصائيا عند مستوى دلالة (0.05) بين متوسطي رتب درجات طلاب المجموعة التجريبية في التطبيقين القبلي والبعدي لبطاقة ملاحظة الأداء لدى طلاب المرحلة الإعدادية لصالح التطبيق البعدي، وجود فرق دال إحصائيا عند مستوى دلالة (0.05) بين متوسطي رتب درجات طلاب المجموعة التجريبية في التطبيقين القبلي والبعدي لاختبار التحصيل المعرفي لدى طلاب المرحلة الإعدادية لصالح التطبيق البعدي، ومن أهم التوصيات هي العمل على توظيف بيئة التعلم المدمج في العملية التعليمية في مراحلها المختلفة لتنمية العديد من المهارات لدى المتعلمين. This research aims to develop educational animation programming skills among middle school students through developing a blended learning environment. The descriptive analytical approach was used in the study and analysis stage, and the quasi-experimental approach was used to measure the impact of developing the blended learning environment to develop educational animation programming skills among middle school students. The current research tools were used, namely: the achievement test to measure the cognitive aspects, and the note card to measure the performance aspects. The research hypotheses and its procedures were presented, and the research sample was chosen, as the current study was limited to a random sample of first year middle school students at Kafr Saadoun Basic Education School, Kotour Educational Administration, Gharbia Governorate, they were randomly divided into two experimental and control groups, and the pre- and post-measurements were applied to two groups. The results resulted in a statistically significant difference at the significance level(0.05) between the average grades of the two groups’ scores in favor of the experimental group in the post-application of the note card, and the presence of a statistically significant difference at the significance level (0.05) between the average grades of the two groups’ scores in favor of the experimental group in the post-application of the cognitive achievement test, and the presence of a statistically significant difference at the significance level (0.05) between the average grades of the experimental group’s students’ grades in the pre- and post-applications of the performance note card among middle school students in favor of the post-application. There is a statistically significant difference at the significance level (0.05) between the average grades of the experimental group’s.
Keywords: الاستراتيجيات التعليمية -- التعلم المدمج -- تنمية المهارات -- طلبة المرحلة الإعدادية